PENERAPAN STRATEGI MANEJEMEN KELAS UNTUK MENINGKATKAN HASIL FOKUS BELAJAR SISWA KELAS V(LIMA) SD NEGERI 1 LATIHAN SPG AMBON - Restiana, Trirestiana; Brivilia Financi Wuarlela; Dina Elma Hukubun; Adriana Elmas; Melvie Talakua; Alcytha Pascallia Heumassy (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This Classroom Action Research (CAR) aims to implement classroom management strategies to improve learning focus outcomes among fifth-grade students at SD Negeri 1 Latihan SPG, consisting of 34 students. The study was motivated by students’ low concentration levels due to distractions, classroom noise, and ineffective classroom management. The strategies implemented included classroom physical arrangement, establishment of rules and routines, positive reinforcement, ice breaking activities, and effective communication, carried out through two cycles based on the Kemmis-McTaggart model. Data collection techniques used were observation, interviews, documentation, and tests, with descriptive qualitative and quantitative data analysis methods. The results showed a significant improvement: observation sheet scores reached 91.6%, the average pretest score increased from 49.41 to a posttest score of 77.06 (t = 9.446, p < 0.01, d = 1.620), indicating a very large effect size. Since the p-value < 0.05, H₀ was rejected and H₁ was accepted, meaning that the treatment significantly improved students’ learning focus outcomes. The success indicator of ≥75% was achieved in Cycle II. The classroom management strategies were effective in creating a conducive learning environment and are recommended for teachers and schools.